2008
DOI: 10.1007/s00125-008-1096-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in retinal microvascular structure

Abstract: Conclusions/interpretation British African Caribbeans appear to have poorer retinal arteriolar endothelial function than white Europeans. Higher BPs explained the narrower arterioles in African Caribbeans; however, patterns of association between arteriolar narrowing and BP suggest the possibility that cerebral autoregulation and/or remodelling might be adversely affected by diabetes in both ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
11
2
Order By: Relevance
“…This could imply that other mechanisms contribute, but it should be noted that our estimate of duration of diabetes is an imprecise measure and is likely to underestimate the true duration of exposure to impaired glucose tolerance leaving the question unresolved. Our findings in diabetic people contrast with previous reports of increased retinal arteriolar narrowing independent of blood pressure in African Americans compared with White Americans in a population study excluding diabetic individuals [47] and narrower retinal arterioles in African Caribbean people in the UK, although in that instance the greater narrowing may have been attributable to higher blood pressures [48]. In the latter study it was also noted that diabetes modified the relationship between arteriolar narrowing and elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 99%
“…This could imply that other mechanisms contribute, but it should be noted that our estimate of duration of diabetes is an imprecise measure and is likely to underestimate the true duration of exposure to impaired glucose tolerance leaving the question unresolved. Our findings in diabetic people contrast with previous reports of increased retinal arteriolar narrowing independent of blood pressure in African Americans compared with White Americans in a population study excluding diabetic individuals [47] and narrower retinal arterioles in African Caribbean people in the UK, although in that instance the greater narrowing may have been attributable to higher blood pressures [48]. In the latter study it was also noted that diabetes modified the relationship between arteriolar narrowing and elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the arteriolar optimality deviation, an indicator of endothelial dysfunction, was recently shown to be greater in African-Caribbeans than whites, independent of conventional risk factors [54].…”
Section: Retinal Architectural Changesmentioning
confidence: 99%
“…1c) is defined as the extent to which the relationship between the parent and daughter arteriolar diameters deviates from theoretically defined optimum [24,25,26]. Griffith et al [27] showed that optimal deviation allows for the uniform distribution of sheer stress on the vessels involved.…”
Section: Methodsmentioning
confidence: 99%